Structure determination of fexofenadine-α-cyclodextrin complex by quantitative 2D ROESY analysis and molecular mechanics studies - Ali, Syed Mashhood (Magnetic resonance in chemistry : MRC, 2012)
Copyright © 2012 John Wiley & Sons, Ltd.